Occupational success? A comparison of dual and school-based training course - Hall, Anja [Verfasser]; Krekel, Elisabeth M. [Verfasser] (My University, 2014)
"In Germany, both dual and school-based vocational education and training lead to qualification for activities at the medium qualifications level. However, what degree of subsequent occupational success is achieved by skilled workers who have obtained their qualifications via the various routes? The 2012 Employee Survey conducted by the Federal Institute for Vocational Education and Training, BIBB, and the Federal Institute for Occupational Safety and Health, BAuA, (BIBB/BAuA Employee Survey) serves as the basis for a comparison of subjective and objective occupational success factors between those who have undergone dual training and those who have completed full-time school-based VET at vocational schools or in the healthcare, education and social services sectors. The results show that any differences perceived to be identifiable between women who have undertaken dual vocational education and training and women who have gone down the school-based pathway are not caused by the different training systems." (authors' abstract; BIBB-Doku)
Keywords: G 1.3.3.1 Qualifikationsverwertung; S 1.3.1 Ausbildung im Dualen System; S 1.3.3 Vollzeitschulische Berufsausbildung; 370; Berufserfolg; Ausbildungsabschluss; Betriebliche Berufsausbildung; Schulische Berufsausbildung; Vergleich; Indikatoren